Identification of growth hormone receptor as a relevant target for precision medicine in low‐EGFR expressing glioblastoma. Issue 7 (8th July 2022) - Verreault, Maïté; Segoviano Vilchis, Irma; Rosenberg, Shai; Lemaire, Nolwenn; Schmitt, Charlotte; Guehennec, Jérémy; Royer‐Perron, Louis; Thomas, Jean‐Léon; Lam, TuKiet T.; Dingli, Florent; Loew, Damarys; Ducray, François; et al.
Abstract: Objective: New therapeutic approaches are needed to improve the prognosis of glioblastoma (GBM) patients. Methods: With the objective of identifying alternative oncogenic mechanisms to abnormally activated epidermal growth factor receptor (EGFR) signalling, one of the most common oncogenic mechanisms in GBM, we performed a comparative analysis of gene expression profiles in a series of 54 human GBM samples. We then conducted gain of function as well as genetic and pharmocological inhibition assays in GBM patient‐derived cell lines to functionnally validate our finding. Results: We identified that growth hormone receptor (GHR) signalling defines a distinct molecular subset of GBMs devoid of EGFR overexpression. GHR overexpression was detected in one third of patients and was associated with low levels of suppressor of cytokine signalling 2 ( SOCS2 ) expression due to SOCS2 promoter hypermethylation. In GBM patient‐derived cell lines, GHR signalling modulates the expression of proteins involved in cellular movement, promotes cell migration, invasion and proliferation in vitro and promotes tumourigenesis, tumour growth, and tumour invasion in vivo. GHR genetic and pharmacological inhibition reduced cell proliferation and migration in vitro. Conclusion: This study pioneers a new field of investigation to improve the prognosis of GBM patients. Abstract : GHR overexpression is observed in one third of GBM patients. GHR overexpression is associated with SOCS2 promoter hypermethylation leading to low levels of SOCS2 expression. GHR signalling promotes cell migration, invasion and proliferation in vitro and promotes tumourigenesis, tumour growth and tumour invasiveness in vivo. Genetic and pharmacological GHR inhibition reduces cell proliferation and migration in vitro.